Evaluating the Impacts of an Undergraduate Mental Health Literacy Course - Christine Zaza; Ryan Christopher Yeung; Gitanjali Shanbhag (Canadian Journal for the Scholarship of Teaching and Learning, 2024)
Mental health literacy is an important factor in caring for mental health; however, in the post-secondary student population, mental health literacy is reported to be low. To address these issues, in 2020, one of the authors [CZ] developed an undergraduate mental health literacy (MHL) course offered through the Faculty of Health, University of Waterloo, to undergraduate students in all Faculties. Building on promising early research conducted by two of the authors in 2021, we conducted three studies to evaluate the impacts of the fully online version of this MHL course. Study #1 was a pre-post study to examine knowledge and attitudes related to mental health literacy (n = 162). Study #2 was a one-month follow-up study to assess continued use of mental wellness strategies practiced during the course (n = 18), and study #3 was a content analysis of part one of the final reflection assignment of the course (n = 32). The pre-post study did not reveal any meaningful changes in knowledge and attitude from Time 1 to Time 2. However, the one-month follow-up study and the content analysis of the final reflection assignment showed multiple meaningful and positive shifts in knowledge, attitudes, and behaviours related to mental health, stigma, self-care, well-being, supporting others with mental health concerns, and the meaning of resilience. In addition, the content analysis revealed that students were sharing course resources with peers, friends, family members and with their community at large. In addition to guiding revisions to strengthen the MHL course under investigation, our findings are relevant to other MHL education initiatives in this population.